Menghidupkan Kembali Budaya Gotong Royong di Lingkungan Sekitar Nagari Tanjuang Bungo - Najmi .; Fatma Riani; Hafiz Akbar; Nadira Despa Maharani; Nazwa Nur Anisa; Rachel Nandisya (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Gotong royong, a traditional cultural value, has long been an integral part of Indonesian community life, including in Nagari Tanjung Bungo. However, its spirit has declined due to modern developments. Through the Community Service Program (KKN), students collaborated with local residents in carrying out mutual cooperation activities aimed at reviving the values of togetherness and social care. These activities included environmental cleaning, public facility repairs, and garden arrangement, involving active participation from various community groups and students. The results showed an increased collective awareness of the importance of cooperation in building a clean and harmonious environment. Furthermore, students gained valuable firsthand experience that enhanced their understanding of social values and community responsibilities. Despite some challenges, effective solutions ensured smooth implementation and fostered positive synergy. This study confirms that preserving gotong royong is key to strengthening solidarity and sustainable community development.